Breakfasts around the Globe - Jennifer Hillan; Claudia Peñuela (EDIS, 2010)
Revised! FCS8714, a 1-page fact sheet by Jennifer Hillan and Claudia Peñuela, provides a matching activity to learn more about breakfasts around the world. Published by the UF Department of Family, Youth and Community Sciences, October 2010.